2005
DOI: 10.1002/adsc.200404295
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(II)‐Azabis(oxazoline)‐Catalyzed Conjugate Reduction of α,β‐Unsaturated Carbonyl Compounds

Abstract: Azabis(oxazolines) prove to be superior ligands for the enantioselective, cobalt(II)-catalyzed conjugate reduction of a,b-unsaturated carbonyl compounds with sodium borohydride. b-Trisubstituted a,b-unsaturated esters and amides as well as g-butenolides are readily converted to their corresponding saturated counterparts with enantioselectivities up to 97% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Pfaltz et al [14] reported the first asymmetric conjugate reduction with a chiral Co semicorrin catalyst and NaBH 4 , followed by Yamada et al [15] using a Co oxoaldiminato catalyst with NaBH 4 , and Reiser et al [16] with CoCl 2 and chiral bisoxazoline ligands. For non-asymmetric reductions, a stoichiometric [Co 2 (CO) 8 ]/H 2 O system, which can promote the conjugate reduction of a,b-unsaturated ketones, was reported by Lee et al [17] We examined the suitability of Co-Bopa catalysts for conjugate reduction of enones in combination with (EtO) 2 MeSiH.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Pfaltz et al [14] reported the first asymmetric conjugate reduction with a chiral Co semicorrin catalyst and NaBH 4 , followed by Yamada et al [15] using a Co oxoaldiminato catalyst with NaBH 4 , and Reiser et al [16] with CoCl 2 and chiral bisoxazoline ligands. For non-asymmetric reductions, a stoichiometric [Co 2 (CO) 8 ]/H 2 O system, which can promote the conjugate reduction of a,b-unsaturated ketones, was reported by Lee et al [17] We examined the suitability of Co-Bopa catalysts for conjugate reduction of enones in combination with (EtO) 2 MeSiH.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[3] Very recently, Reiser et al reported that the azabis(oxazoline) is a superior ligand for cobalt-catalyzed ACR of esters and carboxamides. [4] On the other hand, as for copper catalysts, chiral copper-hydride species generated by reaction of CuCl/NaOtBu/TolBINAP and PMHS (PMHS = polymethylhydrosiloxane) was reported by Buchwald et al in 1999 to show higher enantioselectivity for esters, and the system was then applied to ACR giving optically active cyclopentanones, lactones, lactams, and b-azaheterocyclic acid derivatives. [5] Around the same time, Lipshutz et al also reported that copper catalysts bearing chiral bisphosphine, JOSIAbstract: New asymmetric conjugate reduction of b,b-disubstituted a,b-unsaturated ketones and esters was accomplished with alkoxylhydrosilanes in the presence of chiral rhodium(2,6-bisoxazolinylphenyl) complexes in high yields and high enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Use of Et 3 SiH or EtMe 2 SiH leads to conjugate reduction (1,4-reduction) followed by hydrolysis giving ketones, whereas Ph 2 SiH 2 leads exclusively to 1,2-reduction giving allylic alcohols. Keinan et al also developed the efficient hydrosilative 1,4-reduction systems with palladiumand molybdenum-based catalytic systems, [Pd(Ph 3 P) 4 ]/ ZnCl 2 /Ph 2 SiH 2 and [Mo(CO) 6 ]/PhSiH 3 , respectively. [13] Alternatively, the copper-hydride systems have recently been reported by several research groups, as mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…It seems plausible that these differences in behaviour can be attributed to the different stabilities of the ligand-Cu complexes, which are higher for azabox as demonstrated by theoretical calculations [21] and the better performance and recoverability when immobilized by electrostatic interactions on clays and nafion-like solids [22], in ionic liquid phases [23] or by covalent grafting to organic polymers [24]. Even this higher stability has been pointed out as the reason for the better performance of azabis(oxazoline)-metal complexes as catalysts in other reactions, such as the enantioselective reduction of unsaturated esters with cobalt catalysts, both in homogeneous phase [25] and in recyclable systems [26].…”
Section: Resultsmentioning
confidence: 99%